Influence of a Few More Channels for Voice Support in B3G Multi-Service Traffic in the Presence of Mobility - Paulo, Rui R. (2010)
The analysis of the impact of voice-over-IP into HSPA and LTE multi-service traffic is a challenge. The validation of a Bernoulli-Poisson-Pascal multi-service traffic model in the presence of mobility is explored for different values for the number of channels. A mixture of voice (VOI) and video telephony (VTE) is considered. In a previous work, a critical situation was assumed where the total number of channels was exactly the same as needed by four VTE sessions. However, when few extra channels are added there is a significant reduction on VTE on/off blocking probability. With this few extra resources, VOI can now be easily supported. Since it is supported on top of a system saturated with VTE sessions, Pbonoff decreases 4.6 times for VTE. Since the number of resources is not critical anymore, the range of values of the offered traffic for which the theoretical model agrees with simulation results becomes wider. There is no significative difference between the multi-service traffic results for the seven cell geometry and the roundabout (or ring) cellular topologies in the presence of mobility.